Reliability of novel postural sway task test - Milan Sedliak; Ján Cvečka; Veronika Tirpáková; Stefan Löfler; Nejc Šarabon; Helmut Kern; Dušan Hamar (PAGEPress Publications, 2013)
The purpose of this study was to examine the reliability of parameters obtained from a novel postural sway task test based on body movements controlled by visual feedback. Fifty-nine volunteers were divided into two groups. The first group consisted of young (n = 32, 16 females and 16 males, age: 25.2 ± 3.4 years) and the second group of elderly individuals (n = 27, 17 females and 10 males, age: 75.7 ± 6.9 years). Participants stood in parallel on a computer based stabilographic platform with the feet approximately a shoulder width apart, the toes slightly pointing outwards, the hands placed on the hips. The computer screen was placed approximately 1.5 meter from the platform at a height of subjects’ eyes. An instantaneous visual feedback of participant’s centre of pressure (COP) was given in a form of a blue cross visible on the screen. Participants were instructed to keep the blue cross driven by movements of their hips as close as possible to a predefined curve flowing on the screen. Out of the 6 parameters studied, only the average distance of COP from the curve line and the sum of the COP crossings through the curve line showed high reliability. Correlation between these two highly reliable parameters was -0.89. There was also a statistical difference (p<0.001) between young and elderly in both the average distance of COP from the curve line and the sum of the COP crossings through the curve. To conclude, the novel postural sway task provides a simple tool with relatively low time burden needed for testing. The suggested output parameters measured are highly reliable and easy to interpret.